Zasolenie i zakwaszenie gleb i gruntów miejskich w świetle ochrony ekosystemów w dolinach rzecznych = Acidity and salinity of urban soils in the light of protection of ecosystems in the river-valleys - Greinert, Andrzej; Juszczak, Iwona; Urbanowicz, Małgorzata (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Direcf surrounding of Zielona Góra-city is characterized by the majority of podzolic soils. In accordance with historical notices, pine-forest was dominated form on the described area, however the low-lying areas were afforested with oaks. Characteristic feature for the natural forest podzolic soils is low pH value ofthe top-Layers (0-20cm).
Keywords: 2 Międzynarodowa konferencja "Ochrona i rekultywacja terenów dorzecza Odry: zagospodarowanie zlewni" (21-22.06.2001)